Detection and Land Use/ Land Cover Changes Using Remote Sending and GIS: A Case Study of Bulandshahar District (Uttar Pradesh) - Khan, Mohd. Shahnawaz; Khan, Mohd. Mazhar Ali (National Geographical Journal of India, 2012)
Not available